(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Currently, this study delves into the nutritional and cultural importance of traditional fermented fish products from North-East India, namely Ngari, Hentak, Tungtap, Shidol, and Ngar-Ping. These indigenous culinary delights are not only integral to the local diet but also embody centuries-old food preservation techniques. Rich in proteins, essential fatty acids, vitamins, and minerals, these products offer significant health benefits, including enhanced gut health due to their probiotic contents. Additionally, the fermentation process enhances the bioavailability of nutrients, making these foods nutritionally superior. Their unique flavours contribute to the culinary diversity of the region, while their cultural significance fosters community identity and continuity of traditional practices. This exploration underscores the vital role of fermented fish products in supporting both the nutritional needs and cultural heritage of North-East Indian communities.